Strategi Pemberdayaan Yang Dilakukan Oleh Komunitas WEPOSE (We Different But One Purpose) Terhadap Anak Jalanan Bantaran Rel Wonokromo Melalui Pendampingan Pendidikan - Virdiansyah, Erlang; Arundinasari, Indira (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This research aims to analyze the empowerment strategies for street children conducted by the WEPOSE community in Surabaya City, focusing on educational mentoring as a means to improve the quality of life of street children along the Wonokromo railway tracks. Indonesia, as a developing country, faces complex challenges regarding the existence of street children caused by poor family economic conditions and surrounding environmental influences. Street children face marginalization, high risk levels, and exploitation with limited access to education and health services. This research employs a qualitative descriptive method with a participant observation approach at WEPOSE's main headquarters and its assisted areas, covering 336 street children in five strategic locations. The analytical framework uses Suharto's